Income segregation in The Netherlands - trends and analysis - Aldert De Vries; Ries Van der Wouden (European Regional Science Association (ERSA), 2005)
Dutch society does not accept high levels of income segregation. This tendency has repeatedly been revealed in public opinion surveys. Dutch government intervenes on different levels trying to mix low and high income groups both between cities and suburbs, as well as within city neighborhoods. The question is to what extent the assumptions on actual concentration and differentiation of different income groups hold true if compared to real figures. This paper publishes income data at 500 by 500 meter cells, showing significant spatial patterns of distribution and growth of low and high income groups. Remarkably, high income groups appear to be more segregated than low income groups. All Dutch central city areas have regained high income groups in the period 1995-2000, while the reverse happens in all other city neighborhoods. Despite those tendencies, large parts of the cities have a mixed composition of low, medium and high income groups.
Keywords: 330